Compensatory changes in atrial volumes with normal aging: is atrial enlargement inevitable? - Thomas, Liza; Levett, Kate; Boyd, Anita; Leung, Dominic Y.C; Schiller, Nelson B; Ross, David L (Journal of the American College of Cardiology, 2002)
The aim of this study was to evaluate left atrial volume and its changes with the phases (active and passive) of atrial filling, and to examine the effect of normal aging on these parameters and pulmonary vein (PV) flow patterns. Atrial volume change with normal aging has not been adequately described. Pulmonary vein flow patterns have not been volumetrically evaluated in normal aging. Combining atrial volumes and PV flow patterns obtained using transthoracic echocardiography could estimate shifts in left atrial mechanical function with normal aging. A total of 92 healthy subjects, divided into two groups: Group Y (young <50 years) and Group O (old ≥50 years), were prospectively studied. Maximal (Volmax) and minimal (Volmin) left atrial volumes were measured using the biplane method of discs and by three-dimensional echocardiographic reconstruction using the cubic spline interpolation algorithm. The passive filling, conduit, and active emptying volumes were also estimated. Traditional measures of atrial function, mitral peak A-wave velocity, velocity time integral (VTI), atrial emptying fraction, and atrial ejection force were measured. As age increased, Volmax, Volmin, and total atrial contribution to left ventricle (LV) stroke volume were not significantly altered. However, the passive emptying volume was significantly higher (14.2 ± 6.4 ml vs. 11.6 ± 5.7 ml; p = 0.03) whereas the active emptying volume was lower (8.6 ± 3.7 ml vs. 10.2 ± 3.8 ml; p = 0.04) in Group Y versus Group O. Pulmonary vein flow demonstrated an increase in peak diastolic velocity (Group Y vs. Group O) with no corresponding change in diastolic VTI or systolic fraction. Normal aging does not increase maximum (end-systolic) atrial size. The atrium compensates for changes in LV diastolic properties by augmenting active atrial contraction. Pulmonary vein flow patterns, although diastolic dominant using peak velocity, demonstrated no volumetric change with aging.